2022
DOI: 10.1101/2022.10.05.511059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multidisciplinary approach to the study of artworks: environmental conditions, color palette, microbial colonization and nannofossils inLas Musaspainting

Abstract: Over time, cultural heritage has become a key for comprehending and developing our society at an individual and group level, as it provides fundamental information about our origins, specific temporary space, materials' availability using current technology, artist's intention, and site weather conditions. Here, we investigated the physical characteristics of an Italian large-format artwork diptych, located on the ceiling of the National Theater of Costa Rica, to evaluate its pictorial palette as well as the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…muriae as active fungal contaminants on damaged paintings. Aspergillus tardicrescens and A. magnivesiculatus, here newly detected on paintings, contributed to mixed infections together with xerotolerant A. proliferans (Kavkler et al, 2015;Borrego and Molina, 2019), A. jensenii (Kavkler et al, 2015), and A. versicolor (Sterflinger, 2010), and species of Cladosporium (Calderón-Mesén et al, 2023).…”
Section: Existing Data On the Occurrence Of Xerophilic Fungi Obtained...mentioning
confidence: 75%
See 3 more Smart Citations
“…muriae as active fungal contaminants on damaged paintings. Aspergillus tardicrescens and A. magnivesiculatus, here newly detected on paintings, contributed to mixed infections together with xerotolerant A. proliferans (Kavkler et al, 2015;Borrego and Molina, 2019), A. jensenii (Kavkler et al, 2015), and A. versicolor (Sterflinger, 2010), and species of Cladosporium (Calderón-Mesén et al, 2023).…”
Section: Existing Data On the Occurrence Of Xerophilic Fungi Obtained...mentioning
confidence: 75%
“…Several aspects can be tackled: (i) how to recognize fungal infestation, (ii) how to distinguish them from dust-and air-deposited structures, and (iii) how to find active contaminants and distinguish them from past inactive contaminants. Although advanced software analysis tools allow human-independent recognition of areas of paintings decayed by microorganisms, e.g., MicroorganismPattern software (Calderón-Mesén et al, 2023), decayed areas were identified following "naked-eye" inspections or with the help of an USB microscope. To confirm the infection, we used optical microscopy of tape prints as a non-destructive method of sampling in most of the cases in our study.…”
Section: Several Criteria Have To Be Considered To Address Problemati...mentioning
confidence: 99%
See 2 more Smart Citations